Biosorption of Mn(II) by ripped Citrus paradisi pulp waste. Issue 14 (21st March 2016) - Naveed, Sajida; Bhatti, Haq Nawaz; Kazmi, Mohsin; Ishfaq, Tahir; Ikhlaq, Amir; Fatima, Hira
Abstract: The current exploration presents a primary study on the uptake of Mn(II) by ripped Citrus paradisi pulp waste (RCPW). The effects of various engineering parameters such as biosorbent dose, agitation, contact time, initial concentration, temperature, and different eluents were evaluated. Pseudo-second-order kinetic model fits well with the process, and uptake of Mn(II) by RCPW showed monolayer formation as enumerated by Langmuir's model. Increased temperature enhanced the biosorption capacity indicating endothermic nature of the phenomenon. Among HNO3, H2 SO4, HCl, and EDTA, 0.1 N NaOH was found to be the best desorbing agent.